Clarifying the Task of the Church in a Secular Age - Agolia, Grace Mariette (Lumen et Vita, 2020)
This paper argues that a proper theological understanding of the church-world relationship must avoid the tendency to dichotomize the two. Instead of regarding the world as a godless place, Christians must affirm in faith that the world is fundamentally graced, since it is the product of God’s desire to communicate Godself. First, this paper draws upon the work of philosopher Charles Taylor to elucidate the meaning of “secularity” in the Western context. Then, the paper appeals to Karl Rahner’s theology in exploring the prophetic and dialogical functions of the church with respect to society, which entails the church’s own self-critical task as a listening, discerning, and synodal church. Rather than privatizing faith, the minority status of the church in society allows it to fulfill its mission more authentically as servant and sacrament of God’s kingdom. Finally, this paper proposes that any impingement of the ostensible sacred-secular divide starts with the works of mercy because these directly confront the contingencies and vagaries of human life, touching upon our innate need for one another.